Cervical fluid IL-6 and IL-8 levels in pregnancies complicated by preterm prelabor rupture of membranes - Kacerovsky, Marian; Musilova, Ivana; Jacobsson, Bo; Drahosova, Marcela; Hornychova, Helena; Janku, Petr; Prochazka, Martin; Simetka, Ondrej; Andrys, Ctirad (The journal of maternal-fetal & neonatal medicine, 2015)
UNLABELLED: Abstract Objective: To determine the cervical fluid interleukin (IL)-6 and IL-8 levels in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) and the association of these interleukins with microbial invasion of the amniotic cavity (MIAC) and histological chorioamnionitis (HCA). METHODS: Sixty women with singleton pregnancies were included in this study. Cervical fluid was sampled at the time of admission using Dacron polyester swabs, which were placed into the endocervical canal for 20 s. IL-6 and IL-8 levels were determined by ELISA. The management of PPROM was active management (except for in pregnancies <28 weeks of gestation) and occurs not later than 72 h after the rupture of membranes. RESULT: The women with MIAC had higher IL-6 and IL-8 levels than did the women without MIAC (IL-6: p=0.01; IL-8: p=0.003). There was no difference in IL-6 levels between women with and without HCA (p=0.37). The women with HCA had higher IL-8 levels only in the crude analysis (p=0.01) but not after adjustment for gestational age (p=0.06). The women with both MIAC and HCA had higher levels of IL-6 and IL-8 than did the other women (IL-6: p=0.003; IL-8: p=0.001). IL-8 level of 2653 pg/mL was found to be the best cut-off point in the identification of PPROM pregnancies complicated by both MIAC and HCA with a likelihood ratio of 24. CONCLUSIONS: The presence of MIAC is the most important factor impacting the local cervical inflammatory response, which is determined by IL-6 and IL-8 levels in the cervical fluid. IL-8 levels seem to be a promising non-invasive marker for the prediction of pregnancies complicated by the presence of both MIAC and HCA.
Keywords: dospělí; chorioamnionitida; Pregnancy Complications, Infectious; Body Fluids; Chorioamnionitis; Female; předčasný odtok plodové vody; Interleukin-8; Adult; mladý dospělý; ženské pohlaví; cervix uteri; lidé; non-invasive sample; těhotenství; tělesné tekutiny; Interleukin-6; Fetal Membranes, Premature Rupture; inflammatory response; interleukin-8; Amniotic Fluid; infekční komplikace v těhotenství; plodová voda; amnion; Young Adult; interleukin-6; Pregnancy; Cervix Uteri; Amnion; Humans